STRENGTH PROBLEMS ASSOCIATED WITH TRACK BRIDGE INTERACTION IN PRESENCE OF CONTINUOUSLY WELDED RAIL - Ahammed Ali Asif.K, Dr.Raneesh.K.Y; Mr.Sisir.P (International Journal of Research Science and Management, 2016)
Continuous welded rail (CWR) most widely used. Today increasing the continuous welded rail day to day. Continuous welded rail having less maintenance cost and more life span. This chapter discusses about track bridge interaction which effects on stress and support reaction on rail and deck. Due to temperature variation rail stresses are developed.The present study done by SAP2000,by finite element method (FEM).This report include track-bridge interaction phenomenon, numerical modeling, numerical studies. In numerical study effect of stiffness variation, effect of bridge deck span length variation and effect of temperature variation are computed.